Identification of two hyaluronan-binding domains in the hyaluronan receptor RHAMM. - Bo Yang; Li Zhang; Eva A. Turley (1993)
We have identified two discrete hyaluronan-(HA) binding domains in the HA receptor RHAMM (Receptor for HA-Mediated Motility) that mediates the locomotion of H-rae transformed fibroblasts.A complete RHAMM cDNA (1.43 kilobases (kb)) was expressed as a fusion protein with pGEX-2T in Escherichia coli HBlOl and was shown to bind specifically to both biotin-labeled HA in a transblot assay and to HA-Sepharose.The complete cDNA was truncated with restriction endonucleases from the 3' end resulting in 1.30-, 1.02-, 0.71-, and 0.41-kb cDNAs which were then expressed in HB101.Only the fusion peptide expressed from the complete cDNA and the 1.30-kb cDNA bound to HA indicating that the region located between 1.02-1.30kb of RHAMM cDNA was critical for recognition of this glycosaminoglycan.Deletion of 114 bases in this region virtually eliminated HA binding activity thus defining the major glycosaminoglycan binding region to amino acids 400-434 located near the carboxyl terminus of RHAMM.Two domains containing clusters of basic amino acids were identified within this region.Synthetic peptides mimicking these two domains both inhibited HA binding to the complete 1.43-kb expressed glutathione s-transferase-RHAMM fusion protein, and also directly bound to HA-Sepharose.Random peptides and peptides mimicking other regions in RHAMM did not inhibit HA-RHAMM interactions and bound weakly to HA-Sepharose.Oligonucleotides encoding either of these two peptides were linked to the NHderminal 0.71 kb of RHAMM which encoded a peptide that did not contain HA binding activity.Fusion proteins containing either of these recombinant peptides acquired HA binding activity as assessed with a transblot assay.Thus, we have identified two domains within RHAMM that are responsible for its HA binding activity.Increased synthesis of hyaluronan (HA)' has been associated with the morphogenesis of many tissues (1) and with